Qualification of the activities measured by gamma spectrometry on unitary items of intermediate-level radioactive waste from particle accelerators. (January 2021) - Dyrcz, Patrycja; Frosio, Thomas; Menaa, Nabil; Magistris, Matteo; Theis, Chris
Abstract: In the frame of maintenance, upgrade and dismantling activities, activated equipment are removed from the accelerator complex and require characterization in view of their disposal as radioactive waste. The characterization process consists of a series of radiation measurements, complemented by analytical studies, which quantify the activity of radionuclides inside an object. A fraction of the radioactive waste produced at CERN presents contact dose-rates higher than 100 μSv/h, and can therefore be classified as LILW Waste ("Low and intermediate level radioactive waste"). These objects, due to the activation mechanisms, are often subject to large activity heterogeneities. The quantification of gamma-emitting radionuclides is typically performed by gamma spectrometry, under the assumption of homogeneous distributions of activity within an object. However, this assumption can lead to underestimating the activity value of such radionuclides. In this article we perform a gamma spectrometry qualification in order to quantify the impact of assuming homogenous distribution. Highlights: γ-spectrometry qualification for activity measurement of intermediate-level waste produced in particle accelerators. Quantification of activity heterogeneity effects in radioactive waste. Multiple detector counting to reduce gamma spectrometry uncertainties and perform geometry model optimization. Efficiency calibration with optimized geometries.